PENDAMPINGAN KEPADA PETANI TAMBAK UDANG UNTUK MENINGKATKAN HASIL PANEN PETANI TAMBAK DI DESA WANAYASA, KECAMATAN PONTANG, KABUPATEN SERANG - Saepudin Saepudin; Riky Wijaya; Sahroji Sahroji; Sofiatunisa Sofiatunisa; Nindi Dwi Agustin; Sri Wahyuni; Maulana Yusuf; Nabila Erningsilia Pratiwi (LPPM Universitas Bina Bangsa, 2022)
The aim of this study was to monitor water quality in vaname culture pond and compare the application of different rearing culture system and feeding variations. Four ponds culture were used as vaname (Litopenaeus vannamei) growth place. Measured parameters include physical and chemical factors such as temperature, brightness, pH, DO, salinity, ammonia, and alkalinity, while growth shrimp performance showed by SGR, SR, and FCR. The research result of the water quality parameters shows an adequate range values for all of the ponds and good enough for shrimp growth, and especially an optimum range value presented in pond three and four. Survival rate (SR) both pond 3 and 4 exhibit a good presentation that is more than 80%, whereas pond 1 and 2 were just less than 70% of SR value. The specific growth rate (SGR) presents also a good presentation in Pond 3 and 4 rather than pond 1 and 2. Based on the feed consumption, pond 1 and 2 show high FCR that is more than 1.7 while pond 3 and 4 present smaller FCR value which is less than 1.7. Finally, it could be concludhat application of floc in culture rearing system of pond 3 and 4 increase water quality and production value than pond 1 and 2